Jejunogastric Intussusception: A Rare Complication of Gastric Surgery - Gokhan Cipe; Fatma Umit Malya; Mustafa Hasbahceci; Yeliz Emine Ersoy; Oguzhan Karatepe; Mahmut Muslumanoglu (Case Reports in Surgery)
Jejunogastric intussusception is a rare complication of gastric surgery. It usually presents with severe epigastric pain, vomiting, and hematemesis. A history of gastric surgery can help in making an accurate and early diagnosis which calls forth an urgent surgical intervention. Only reduction or resection with revision of the previously performed anastomosis is the choice which is decided according to the operative findings. We present a case of JGI in a patient with a history of Billroth II operation diagnosed by computed tomography. At emergent laparotomy, an efferent loop type JGI was found. Due to necrosis, resection of the intussuscepted bowel with Roux-en-Y anastomosis was performed. Postoperative recovery was uneventful.